Contenidos De Celulosa Y Lignina En Restos Lignino- Celulósicos De Gran Tamaño (Necromasa) En Un Bosque Templado De Antiguo Crecimiento Del Centro-Sur de Chile - Pinargote, Carlos Belezaca; Bórquez, Roberto Godoy; Pilozo, Darwin Salvatierra; Arévalo, María Cadme; Flores, Eduardo Valenzuela; Tobar, Rolando López; Campusano, Diana Delgado; Mite, Renato Baque; Anangonó, Roberto Herrera; Montufar, Carmen Vásconez; Barros, Tito Bohórquez (European Scientific Journal, ESJ, 2016)
The evaluation of volume, necromass, states of decay, solubility, and cellulose and lignin content in coarse woody debris (RLC) accumulated in an evergreen temperate forest of old-growth in the Puyehue National Park, South-Central Chile. Ten plots of 900 m2 each, were quantified for RLC (≥ 10 cm diameter). For necromass quantification was used a scale of five categories/states of decay, necromass (1 = lowest and 5 = highest degradation). 632 m3 ha-1 of deadwood (= 231,5 Mg ha-1 of necromass) was found, mainly represented by Nothofagus betuloides (95,2%). The wood with the most advanced state of decay (state 5) showed a greater solubility, increasing of 273,7 and 818,6 times more soluble than 1, for N. betuloides and S. conspicua, respectively. Cellulose content decreased to 91%, while the lignin increased 248% and 142% in wood decay of N. betuloides and S. conspicua, respectively. These results demonstrate the importance of RLC in the biogeochemistry of remote forest ecosystems of old-growth in Southern Chile.